Efficacy and safety of Shexiang Baoxin pill (MUSKARDIA) in patients with stable coronary artery disease: a multicenter, double-blind, placebo-controlled phase IV randomized clinical trial. Issue 2 (20th January 2021) - Ge, Jun-Bo; Fan, Wei-Hu; Zhou, Jing-Min; Shi, Hai-Ming; Ji, Fu-Sui; Wu, Yang; Zhao, Yu-Lan; Qian, Jun; Jin, Yuan-Zhe; Liu, Ying-Wu; Wang, Sheng-Huang; He, Sheng-Hu; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Background: The Shexiang Baoxin Pill (MUSKARDIA) has been used for treating coronary artery disease (CAD) and angina for more than 30 years in China. Nevertheless, methodologically sound trials on the use of MUSKARDIA in CAD patients are scarce. The aim of the study is to determine the effects of MUSKARDIA as an add-on to optimal medical therapy (OMT) in patients with stable CAD. Methods: A total of 2674 participants with stable CAD from 97 hospitals in China were randomized 1:1 to a MUSKARDIA or placebo group for 24 months. Both groups received OMT according to local tertiary hospital protocols. The primary outcome was the occurrence of a major adverse cardiovascular event (MACE), defined as a composite of cardiovascular death, non-fatal myocardial infarction (MI), or non-fatal stroke. Secondary outcomes included all-cause mortality, non-fatal MI, non-fatal stroke, hospitalization for unstable angina or heart failure, peripheral revascularization, angina stability and angina frequency. Results: In all, 99.7% of the patients were treated with aspirin and 93.0% with statin. After 2 years of treatment, the occurrence of MACEs was reduced by 26.9% in the MUSKARDIA group (MUSKARDIA: 1.9% vs . placebo: 2.6%; odds ratio = 0.80; 95% confidence interval: 0.45–1.07; P   =  0.2869). Angina frequency was significantly reduced in the MUSKARDIA group at 18 months ( P  = 0.0362). Other secondary endpoints were similar between the two groups. The rates of adverse events were also similar between the two groups (MUSKARDIA: 17.7% vs . placebo: 17.4%, P  = 0.8785). Conclusions: As an add-on to OMT, MUSKARDIA is safe and significantly reduces angina frequency in patients with stable CAD. Moreover, the use of MUSKARDIA is associated with a trend toward reduced MACEs in patients with stable CAD. The results suggest that MUSKARDIA can be used to manage patients with CAD. Trial registration: chictr.org.cn, No. ChiCTR-TRC-12003513